(Digital) Privacy - Fernández Barbudo, Carlos (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The development of information technologies, and in particular the Internet, has led to the emergence of new social concerns that raise the impossibility of preserving privacy in the digital sphere. This contribution addresses, in historical perspective, the formation of a new socio-political concept of privacy that has replaced the previous one. To this end, the main elements that differentiate both are presented and what are the fundamental sociotechnical transformations that have enabled this conceptual change. The development of the text will lead to defend the suitability of a political view on privacy and ends with the presentation of some recent proposals that advocate understanding privacy as a collective problem.